DAUN BINAHONG UNTUK PENYEMBUHAN LUKA - Christ Roviaci Toban; Rr Fitriyana Kesumaningsih; Widiyono (MEDIA ILMU KESEHATAN, 2012)
Background: Wound is defined as an epithelial integrity damage of skin or separation of the normal anatomic structure of tissues due to sharp or blunt trauma, temperature changes, chemicals, explosions, electric shock or animal bite. The process of wound healing begins with the inflammatory process which is an important phase in wound healing. In the processof inflammation, white blood cells through a process would kill bacteria and debris using it’s neutrophils, therefore antibacterial or antimicrobial necessary to assist the process. One common action that is practiced by the people is to utilize the binahong leaf. According to Rawat et al. binahong leaves contain antimicrobial which is reactive to infecting bacteria in cluding Pseudomonas aeruginosa, which is harmful germs in the wound. Objective: This study aims to determine the benefits of binahong leaf in the process of wound healing (inflammatory phase) Methods: This type of research was an experimental quasy design with prospective cohortand quantitative approaches. Number of samples in this study were 10 mice (Mus musculus). Object of study was divided into 2 groups: group 1 was the control group and group 2 was agiven treatment group. Each group was consisted of 5 mice. Observations began after subjects were given wound and continued to take place every 12 hours for 4 days. Results; According to the analysis result, The average length of inflammatory phase in the control group are 84 hours where as the length of inflammatory phase in the treatment grou pare 45,6 hours. Between those average lengths of the inflammatory phase in the 2 groups,there is an interval of 38,4 hours. It means that the treatment group has 38,4 hours shorter length of inflammatory phase compared to control group. Conclusion: From the results of analysis and the discussion, it is found out that binahong leave is prove useful in the process of wound healing. Keywords: Binahong, inflammation, wound healing